Managerial Overconfidence and Leverage Decision. The Moderating Effect of Human Governance in Malaysia - Irene, Wei Kiong Ting; Noor Azlinna, Azizan; Kweh, Qian Long (Inderscience Enterprises Ltd., 2016)
This paper examines the firm's leverage decision from new perspectives, namely managerial overconfidence and human governance. The balanced panel sample covers Malaysian public listed companies from 2002 to 2011. The objectives of this study are to investigate the relationship between managerial overconfidence and its moderating effect on the relationship between CEO personal characteristics and firm leverage decisions. The findings are as follows: 1) CEO overconfidence, age and prior experience are significantly negative related to leverage; 2) The higher the education, the higher the debts; 3) CEO tenure is significantly positive related to leverage; 4) The higher the overconfidence level in presence of their age, the more the debts; 5) Firm leverage is lower when CEO with higher educational degree has higher confidence level. The result of the paper can fill the gap in the literature on the managerial overconfidence and its relationship with leverage decision of Malaysian public listed companies.